(3GdbQGfGJ hGdEJUGdGJ aj GdHQhL GdCKfi YTQs - (3Sgd Hf HTQ Hf MHjH Hf gGfj, CHh YKeGf GdESQGFjdj,J (B235 (3g` s
(3ChdgG (B:s
(3GdTgQ Odjd eNQL ef Odjdjf gh TgQ GdSYGOI GdOGd Ydi GdeGd TgQ GdSYGOI jDNP HGdfgGQ ef GdTeS Edi GdbeQ s
(3BNQgG (B:s
(3ebGQfI GdbeQ dYWGQO jOd (B_ (3hGddg CYde (B_ (3Ydi YOh HGdTGe hYOGhI GdCe hRjGOI GdCegGJ hcKQI GdWjQ hGdSec Je GdcdGe ai GdbQGfGJ hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B142 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B283s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B252 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B396 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI (B_ (3GdEScfOQjI (B(1291(3H(B(2)) s
Keywords: (3Gdadcs